Efficacy of radiotherapy combined with atezolizumab or docetaxel in patients with previously treated NSCLC - Xu, Junzhu; Wang, Haitao; Zhang, Chi; Jin, Su Han; Chen, Xiaofei; Tan, Fangya; Frey, Benjamin; Hecht, Markus; Sun, Jian Guo; Gaipl, Udo; Ma, Hu; Zhou, Jian Guo (iScience, 2024)
Radiotherapy showed synergy with immunotherapy, yet the comparative effectiveness of combining immunotherapy (iRT) or chemotherapy (CRT) after platinum therapy failure in advanced non-small cell lung cancer (NSCLC) remains unexplored. We analyzed 163 patients (iRT: n = 120 vs. CRT: n = 43) eligible for combination radiotherapy. Before matching, median overall survival (OS) was significantly longer in iRT group (7.79 vs. 4.57 months, hazard ratio [HR]: 0.62, 95% confidence interval [CI]: 0.41–0.94, p = 0.024). After 1:2 propensity score matching (PSM) and inverse probability of treatment weighting (IPTW), iRT group showed improved OS, consistent with unmatched analysis (PSM, p = 0.033 and IPTW, p = 0.035). Exploratory analysis suggested that PD1+, central memory PD1+, and effector memory PD-L1+ CD4+ T cells were strong predictive biomarkers for iRT-treated patients (POS = 0.025, POS = 0.002, POS = 0.010, respectively). Proliferative CD4+ T celllow was a prognostic (POS = 0.008) and predictive biomarker for iRT (POS < 0.001). Our work revealed iRT was prolonged OS in previously treated advanced NSCLC patients. Additionally, proliferative CD4+ T cell served as prognostic and predictive biomarkers.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Cancer; Public health